Hydrothermal experiments involving methane and sulfate: Insights into carbon isotope fractionation of methane during thermochemical sulfate reduction. (November 2020) - He, Kun; Zhang, Shuichang; Wang, Xiaomei; Mi, Jingkui; Hu, Guoyi
Highlights: TSR of methane occurred in hydrothermal experiments with sulfate at 400–600 °C. TSR resulted in the evident enrichment of 13 C for CH4 but had limited effect on δ 2 H1 . Kinetic 13 C isotope fractionation factor (α) for methane TSR ranges from 0.98 to 0.99. The conversion of CH4 via TSR in the Puguang gas field is less than 20%. Abstract: To understand the isotope fractionation of methane (CH4 ) during thermochemical sulfate reduction (TSR), isothermal pyrolysis of CH4 /N2 gas involving gypsum + MgCl2 and MgSO4 solutions were conducted in a gold-tube system. CH4 was oxidized to generate H2 S and CO2 via TSR in the hydrothermal experiments with sulfate. The δ 13 C1 becomes more enriched with the conversion of CH4 . However, there is no evident enrichment of 2 H for CH4 during TSR under hydrothermal conditions. Ab initio quantum calculations based on Density Functional Theory (DFT) demonstrate that the kinetic isotope effect (KIE) rather than the thermodynamic equilibrium isotope effect (EIE) governs the 13 C fractionation during methane TSR. The kinetic 13 C fractionation factor (α) for TSR of CH4 involving SO4 2− and HSO4 − is 0.960–0.992 between 0 °C and 600 °C. Combining these experimental results, α for methane TSR was in the range 0.98–0.99 with an average value of 0.985. Based on these results, the extent of methane TSR for natural gas in the Puguang gas field in the northeastern Sichuan Basin was determined via the evolution of δ 13 C1 . Geological extrapolation of the kinetic parameters and KIE suggests that the conversion of CH4 via TSR in the P2 ch -T1 f Formations in this gas field is <20%.